Locus BoLA-DRB3 is just an ordinary site of the polygene when explaining genetic variance of somatic cell count and milk yield. Issue 4 (3rd September 2015) - Oprzadek, Jolanta; Sender, Grazyna; Pawlik, Adrianna; Lukaszewicz, Marek
Abstract : The study aimed at clarifying the problem of the hitherto contradictory results regarding usefulness of BoLA-DRB3 locus as a marker in selection against mastitis and for milk yield. Treating the BoLA-DRB3 locus effect as random was proposed in place of considering it fixed. Somatic cell counts and milk yields recorded monthly on a test day (22 424) of 619 Polish Holstein cows genotyped for BoLA-DRB3 were analysed with an animal model including a random effect for genotype at this locus. The BoLA-DRB3 alleles were defined as restriction patterns obtained with three endonucleases. Two alternative BoLA-DRB3 additive genotype (co)variance structures were constructed for 161 genotypes recorded. One was based on the allelic similarity of the genotypes resulting in element values of 0 (no common allele), 0·5 (one allele in common), and 1 (diagonal). The other considered restriction site similarity (up to 3 in 1 allele) giving element values of 0 (no common restriction sites) and then increasingly in steps of 1/6 up to 6/6 (diagonal), where the numerator represents the number of common sites between genotypes. The DRB3 variance component for the natural logarithm of somatic cell count did not exceed 0·006 of the polygenic additive component or 0·003 for milk yield. Hence, unless we fail to detect the causative site or to properly define traits being the projection of a site, the effect of the genotype at the BoLA-DRB3 locus does not explain variation in somatic cell count and milk yield at a degree expected of a genetic marker.